X-Ray Diffraction and TG-DTA Studies of Archaeological Artifacts Recently Excavated in Salamankuppam Tamilnadu - R. Sudha1 and R. Hemamalini2, G. Velraj1*, (Recent Research in Science and Technology, 2010)
The present study deals with the characterization of pottery samples which were recently excavated in Salamankuppam, Tamilnadu. The samples were subjected to X-ray diffraction and thermal studies. The mineralogical composition of the potteries were found using XRD. By noting the difference in the mineral composition of the samples the firing temperature is interpreted. TG-DTA is used as the complementary technique to find the firing temperature.